Individuals with aphasia generate larger adaptive and corrective responses to suddenly introduced auditory perturbations - Basciano, Alexis; Chao, Sara-Ching; Gomez, Amy; Daliri, Ayoub; Rogalsky, Corianne (Frontiers in Human Neuroscience, 2025)
IntroductionPersons with aphasia (PWA) experience changes to feedback and feedforward speech motor control, though the impact on these subsystems has not yet been explored using different perturbation schedules. Here, we examine the magnitude of auditory-motor adaptive and corrective responses together in PWA using gradually and suddenly applied perturbation schedules.MethodsNine PWA and 12 neurotypical adults of similar age to the PWA (NT) completed gradual and sudden altered auditory feedback (AAF) paradigms to measure adaptive and corrective responses to formant perturbation (formants of/ε/shifted toward formants of/æ/). As a measure of the feedforward system, we calculated adaptive responses using the formant changes in the first 100 ms of production. As a measure of the feedback system, we calculated corrective responses based on the differences between the later portion of the production (200–300 ms) and the early portion of the vowel (0–100 ms). Our analyses revealed significant interactions between group and perturbation schedule.ResultsAdaptive and corrective responses of PWA were more similar to those of the NT group in the sudden perturbation schedule. Single-case comparisons of each PWA to the NT group identified different impairment patterns in adaptive and corrective responses during gradual and sudden AAF paradigms within PWA.DiscussionThese findings suggest that measuring adaptive and corrective responses using an adaptation paradigm in PWA is both viable and informative, as the PWA exhibited different impairments in adaptive and corrective responses across the two perturbation schedules. Outcome differences in response to sudden versus gradual perturbations for the PWA may be explained by difficulties with the detection of auditory errors during speech. Perhaps a sudden perturbation schedule improves the adaptive and corrective abilities of PWA by increasing their agency over their speech errors. More studies are needed to further elucidate the critical mechanisms of auditory-motor adaptive and corrective responses in PWA.